2017
DOI: 10.1016/j.jsat.2016.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Quality of care measures for the management of unhealthy alcohol use

Abstract: There is a paucity of quality measures to assess the care for the range of unhealthy alcohol use, ranging from risky drinking to alcohol use disorders. Using a two-phase expert panel review process, we sought to develop an expanded set of quality of care measures for unhealthy alcohol use, focusing on outpatient care delivered in both primary care and specialty care settings. This process generated 25 candidate measures. Eight measures address screening and assessment, 11 address aspects of treatment, and six … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…Still, even among existing mental health process measures that could be reported, not all have been validated 25,26,[33][34][35][36][37][38][39] .…”
Section: Current State Of Measuring Mental Health Care Qualitymentioning
confidence: 99%
“…Still, even among existing mental health process measures that could be reported, not all have been validated 25,26,[33][34][35][36][37][38][39] .…”
Section: Current State Of Measuring Mental Health Care Qualitymentioning
confidence: 99%
“…Several other NQF-endorsed treatment performance measures are related to screening for tobacco use in inpatient settings. In addition, an expert panel convened by the RAND Corporation has suggested that detailed specification development and pilot testing would be appropriate for a potential AUD-related quality measure on screening for substance use, including tobacco use, in individuals with an Alcohol Use Disorders Identification Test-Concise (AUDIT-C) score of greater than or equal to 5 (Hepner et al 2017). The American Society of Addiction Medicine also has proposed a measure on screening for tobacco use disorder (American Society of Addiction Medicine 2014).…”
Section: Quality Measurement Considerationsmentioning
confidence: 99%
“…Brief counseling is described as at least one session of "a minimum of 5-15 minutes, which may include: feedback on alcohol use and harms; identification of high risk situations for drinking and coping strategies; increased motivation and the development of a personal plan to reduce drinking" (National Quality Measures Clearinghouse 2016). An expert panel convened by the RAND Corporation has suggested a number of potential AUD-related quality measures that would be appropriate for detailed specification development and pilot testing; many of these use specific threshold scores on the AUDIT-C as a method for identifying individuals who are appropriate for the use of the measure (Hepner et al 2017).…”
Section: Quality Measurement Considerationsmentioning
confidence: 99%
See 2 more Smart Citations